Rethinking the Role of the State in Employment Relations for a Neoliberal Era. (May 2021) - Howell, Chris
Over the past 30 years, state intervention to reshape employment relations has become a generalized feature of contemporary capitalism. A broad neoliberal reconstruction of the market order has gone hand in hand with a more active state. In this article the author argues that liberalization in the sphere of employment relations could not have taken place without a more active state. Building on a regulation theory framework and an elaboration of the concept of neoliberalism as the regulatory infrastructure of emergent growth models, the author examines how the widespread shift from wage-led growth to other forms of growth across the advanced capitalist world has encouraged changes in the role of the state in the regulation of employment relations. These roles include market making, individual employment regulation in place of collective regulation, state-directed social pacts, and redrawing the boundaries between work and non-work. The article concludes with an explanation for continuing variations in employment relations.